Envirocat EPZG Mediated Synthesis of 3,4-Dihydropyrano[c]chromene Derivatives Under Microwave Irradiation in Solvent-free Conditions - Surekha N. Deshmukh; Laxmikant D. Chavan; Murlidhar S. Shingare (Orbital: The Electronic Journal of Chemistry, 2021)
A Envirocat EPZG mediated method is developed for the synthesis of 3,4‐dihydropyrano[c]chromene derivatives under microwave irradiation by three component cyclocondensation of 4‐hydroxycoumarin, malononitrile and aromatic aldehydes. The process has been carried out under solvent-free conditions in the presence of very small amount of Envirocat EPZG. Use of ecofriendly readily available catalyst and green reaction media makes this methodology simple, safe, and cost effective. Mild reaction conditions, easy workup procedure, excellent yields and short reaction times are some remarkable features of this work.DOI: http://dx.doi.org/10.17807/orbital.v13i1.1517